ABYSS. III. Observing Accretion Activity in Young Stars Through Empirical Veiling Measurements - Serat Saad; Marina Kounkel; Keivan G. Stassun; A. Roman-Lopes; C. Román-Zúñiga; Jinyoung Serena Kim; Jonathan C. Tan; R. López-Valdivia (The Astronomical Journal, 2025)
Stellar accretion plays an important role in the early stages of stellar evolution, particularly in Classical T Tauri Stars (CTTSs). Accretion of a CTTS can be related to different physical parameters such as effective temperature ( T _eff ), age, abundance of hydrogen, etc. We can infer how accretion works by examining it across different wavelength regions. Accretion can be traced using veiling, a parameter that measures how excess emission from accretion affects the photospheric spectrum of CTTS. In this study, we selected a sample of CTTSs, Weak-line T Tauri Stars, and field stars, observed as a part of the SDSS-V Milky Way Mapper using the Baryonic Oscillation Spectroscopic Survey spectrograph. We measured veiling for CTTSs through comparing them to theoretical spectra. Next, we assessed the effect of veiling on different stellar properties, including wavelength, H α emission, effective temperature, and age. We investigated how veiling changes with these parameters and what the physical reasons behind the changes can be. Finally, we evaluated how our findings align with existing accretion shock models. This study highlights veiling as a critical diagnostic tool for understanding accretion in young stars.